Phenotypic and genotypic antimicrobial resistance in Escherichia coli strains isolated from household dogs in Chile - Galarce, Nicolás; Arriagada, Gabriel; Sánchez, Fernando; Escobar, Beatriz; Miranda, Mauricio; Matus, Sofía; Vilches, Rocío; Varela, Camila; Zelaya, Carlos; Peralta, Josefa; Paredes Osses, Esteban.; González Rocha, Gerardo.; et al. (Frontiers Media SA, 2023)
Introduction: Antimicrobial resistance (AMR) is a major threat to animal and public health worldwide; consequently, several AMR surveillances programs have been implemented internationally in both human and veterinary medicine, including indicator bacteria such as Escherichia coli. However, companion animals are not typically included in these surveillance programs. Nevertheless, there have been reports of increasing levels of antimicrobial resistance in E. coli strains isolated from dogs worldwide. In Chile, there is limited information available on AMR in E. coli isolated from companion animals, which prevents the establishment of objective prevention and control measures. Methods: For this reason, the aim of this study was to characterize the phenotypic and genotypic AMR of E. coli strains isolated from healthy household dogs in Chile. For this purpose, a multi-stage sampling was carried out in the Metropolitan Region of Chile, obtaining samples from 600 healthy dogs. These samples were processed using traditional bacteriology and molecular techniques to isolate E. coli strains. We assessed the minimal inhibitory concentration of 17 antimicrobials and conducted a search of six antimicrobial resistance genes, as well as class 1 and 2 integrons, in the isolated strains. Results: Two-hundred and twenty-four strains of E. coli were recovered, and 96.9% (n = 217) showed resistance to at least one drug and only 3.1% (n = 7) were susceptible to all analyzed antimicrobials. Most strains were resistant to cefalexin (91.5%, n = 205, 1st-generation cephalosporin), followed by ampicillin (68.3%, n = 153) and cefpodoxime (31.3%, n = 70, 3rd-generation cephalosporin). Moreover, 24.1% (n = 54) tested positive for extended-spectrum-β-lactamases and 34.4% (n = 77) were multidrug resistant. As for the AMR genes, the most detected was qnrB (28.1%, n = 63), followed by blaCTX-M (22.3%, n = 50), and blaTEM-1 (19.6%, n = 44). Additionally, 16.1% (n = 36) harbored class 1 integrons. Our study shows that E. coli strains isolated from healthy household dogs exhibit resistance to several relevant drugs and also antimicrobial resistance genes considered critical for human health. These results can be used as a starting point for the prevention and control of antimicrobial resistance from companion animals. This background should be considered when formulating future resistance surveillance programs or control plans in which companion animals must be included.
Keywords: Antimicrobial resistance; Genotypic; Phenotypic; Escherichia coli; Perros; Resistencia a las drogas